Ratio of Vascular Pedicle Width and Thoracic Diameter to Differentiate Cardiogenic and Non-Cardiogenic Pulmonary Edema - Afifi, Rahmi; Fachri, Achmad; Madjid, Amir Sjarifuddin; Prihartono, Joedo; Prasetyo, Marcel; Christian, Andreas (UI Scholars Hub, 2022)
Background: Excess intravascular volume evaluation is essential in the intensive care unit (ICU); however, clinical information to differentiate cardiogenic and non-cardiogenic pulmonary edema has been proven ineffective. Thus, this study aimed to distinguish cardiogenic from non-cardiogenic pulmonary edema using the ratio of vascular pedicle width (VPW) to thoracic diameter (VPTR). Methods: This cross-sectional study was conducted based on secondary data from chest radiographs of 100 patients with clinical symptoms of pulmonary edema in the ICU from January 2013 to December 2015. Cardiogenic and non-cardiogenic pulmonary edema were distinguished using VPW and cardiothoracic ratio measurements (CTR). VPTR was measured to differentiate between the two types of pulmonary edema, and the cut-off value was obtained using a receiver operating characteristic curve. Results: This study revealed a prevalence of 21% and 79% for cardiogenic and non-cardiogenic pulmonary edema, respectively. A VPTR cut-off value of 25.1% with a sensitivity of 90% and specificity of 86%, may distinguish cardiogenic from non-cardiogenic pulmonary edema. Conclusions: VPTR is an alternative method to differentiate between cardiogenic and non-cardiogenic pulmonary edema, and this ratio measurement is useful in cases where radiograph films are not standardized.